Apuntes sobre el léxico de un inventario decimonónico de la Real Maestranza de Caballería de Ronda - Torres Martínez, Marta (El Colegio de México, 2019)
The present research takes as its subject of study an inventory of goods and chattels from 1894 arranged in a notarial protocol, which has been preserved in the Archive of the Real Maestranza de Caballería at Ronda.The main objective is twofold: to publish unknown archive data and to list the documented lexicon and contrast it with other lexicographical sources of the time. Specifically, this study examines the treatment of our corpus in the lexicographical history of Spanish, as well as in specialised catalogues such as the Gran diccionario taurómaco (1896) by Sánchez de Neira or the Vocabulario taurino (1900) by Casellas, among others. In short, this work intends to contribute to a better understanding of the historical lexicon of Spanish, in the specific sphere of bull-fighting.